Second Generation Ethanol from Residual Biomass: Research and Perspectives in Ecuador - Barriga, Enrique Javier Carvajal; Guamán-Burneo, Cristina; Barahona, Patricia Portero; Salas, Edgar; Tufiño, Carolina; Bastidas, Bernardo (IntechOpen, 2013)
None